Estado de alarma: ¿para qué? Reflexiones sobre la utilidad de este estado excepcional tras las Sentencias del Tribunal Constitucional 148/2021 y 183/2021 - GUILLERMO VILLAR CRESPO (Revista Vasca de Administración Pública)
As a result of the publication of the Judgements of the SpanishConstitutional Court no. 148/2021 and no. 2021, the state of alarm has beenreconfigured in the Spanish legal system. The established doctrine opens a newscenario regarding the application and effects of this exceptional state, as wellas its connection with the Spanish ordinary crisis regulations. The purpose ofthis paper is to analyze the utility of this exceptional state in the light of suchdecisions. The paper addresses the referred matter focusing on the historicalevolution of the legal crisis instruments in Spain, on the original configurationof the state of alarm, and, of course, on the new position of this institution for itsfuture use.